Cyclicality and the relationship between neuroticism, communication, and relationship satisfaction in cohabiting couples - Lindstrom, Rachel A. (Kansas State University, 2013)
The present study sought to extend the research on cyclical, or on-again/off-again relationships, by examining whether a history of cyclicality moderated the association between neuroticism and relationship satisfaction. A second goal of this study was to examine the direct and indirect effects of neuroticism on relationship satisfaction through communication. The sample consisted of cohabiting cyclical (n = 1,055) and noncyclical (n = 2,527) couples from a larger dataset collected by the RELATE Institute. Results showed that cyclical partners reported higher levels of neuroticism, higher levels of conflict, lower levels of positive communication, and lower levels of relationship satisfaction than noncyclical couples. Direct actor paths from neuroticism to satisfaction were significant for cyclical and noncyclical females and males. Only the direct partner path from female neuroticism to male satisfaction was significant, and was only significant for cyclical couples. All indirect actor and partner paths were significant for cyclical and noncyclical females and males. Further, a history of cyclicality significantly moderated the direct paths from male communication to male and female relationship satisfaction, indicating this relationship is stronger for cyclical couples.
Keywords: Cohabitation; Relationship dissolution; Relationship satisfaction; Neuroticism; Psychology (0621)